Hubungan Status Imunisasi dan Riwayat Kontak dengan Kejadian Campak Pada Balita di Kabupaten Sukoharjo - Fatimah Ramadhani, Nuri, Bejo Raharjo, SKM, M.Kes, Kusuma Estu Werdani, SKM., M.Kes (2016)
The relationship immunization status and history of contact with measles incidence in infants in Sukoharjo district Measles is one of many contagious disease that poses a health problem of infants and children. Measles can caused the death, which is triggered by complications of other diseases.In the year 2015-2016 as many as 57 cases of confirmed measles cases. The research objective was to determine the relationship immunization status and contact history of measles disease incidence in toddlers in Sukoharjo district. The study with case control design. Respondents from the group of cases, were drawn from toddlers with measles aged 9-59 months totaling 43 toddlers. Comparison of cases and controls 1: 1. The majority of toddlers in the case group aged 24-59 months (53.5%), not exclusively breast-fed (53.5%), were given vitamin A (93.0%) and have a good nutritional status (100%). Chi square test analysis results showed that there is a relationship immunization status (p = 0.002; OR = 4.449; 95% CI = 1.776 to 11.114) and contact history of measles is (p = 0.038; OR = 2.991; 95% CI = 1.157 to 7.731) with the measles incidence in toddlers. Community are expected to seek information from a reliable source such as clergy/MUI concern that immunization is allowed and understanding on the transmission of measles by asking the health worker. The other researchers can continue this research by analyzing the risk factors that have not been researched including exclusive breastfeeding, vitamin A and nutritional status. keywords : Immunization status, contact history and measles incidence